(untitled) (World Economics and Finance Bulletin, 2024)
The importance of lease contracts has increased in the present time through leasing many economic units of their core assets in their activities as a source of financing. Lease contracts have witnessed increased interest from professional accounting organizations with the development of lease contracts, as a number of accounting standards related to the recognition, presentation, and disclosure of lease contracts have been issued. The IFRS 16 financial reporting standard is the latest of these standards, and one of its main objectives is to improve the quality of financial reporting for economic entities." This study aims to reveal the impact of implementing the IFRS 16 lease standard on financial ratios. The researcher selected external auditors working in major audit firms in Iraq, where the research was applied to companies listed on the Iraq Stock Exchange. The research concluded that the application of the IFRS 16 lease standard affects the financial ratios of companies listed on the Iraq Stock Exchange